Antibacterial and Wound Healing Activity of Papuyu Fish (Anabas Testudineus) Mucus - Erwin Rosadi; Lia Yulia Budiarti; Nor Admi Zayanti; Isnaini Isnaini (Journal of Wetlands Environmental Management, 2022)
One of the local fish resources in South Kalimantan is Anabas testudineus fish. It is known that A. testudineus fish mucus has antibacterial activity, but this study only looked at the inhibitory of fish mucus. Until now, there has been no test for the Minimum Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) of A. testudineus fish mucus. One of the bacteria that infect wounds is S. aureus. MIC and MBC obtained are used as a reference in determining the concentration of A. testedineus fish mucus gel for wound healing activity test. This study aimed to determine the MIC and MBC of A. testudineus fish mucus in S. aureus and analyze the wound healing activity of A. testudineus fish mucus. MIC and MBC using turbidity test. In this research, 3 fish mucus gel formulas are made. Wound healing activity test on Wistar rats that were given wound initiation with a diameter of 1.5 cm, and were observed after 7 days of treatment. Observations were made covering the area of the wound using image J and histology of rat skin. The results showed that MIC and MBC of A. testudineus fish mucus were 21.875%. Fish mucus gel formula was made into concentrations of 10%, 20% and 40%. The results of the wound healing test showed that giving A. testudineus fish mucus caused a decrease in the area of the wound but based on histology of the skin, the inflammation still occurred.